Мережна безпека, системи виявлення та протидії атакам, відмовостійкість мереж - Тертичний, В. О. (ХНУРЕ, 2020)
In recent years, the number of deliberate interventions (hacker or cyber attacks) in the work of information systems of all state and commercial structures has sharply increased in Ukraine. In almost all cases, after the implementation of hacker attacks, the work of enterprises is blocked from several hours to several days, which leads to significant financial losses. The article describes the main points of network security in general, It also talks about network resiliency. A set of measures to protect the network was also proposed